Metal surface rusty anticorrosive paint

By using rust-resistant coatings containing nanocarbon secondary doped polyaniline composite materials and long-acting rust converters on marine building steel structures, the existing anti-rust rust converters have been solved, with high toxicity, poor construction economy, poor permeability and general protection against microbial corrosion, which has achieved efficient and economical anti-corrosion effects and extended the service life of the steel structure.

CN119552558APending Publication Date: 2025-03-04QINGDAO HIGHFLY SAFETY TECH CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411908492.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing anti-rust-turning agents have high toxicity, poor construction economy, poor permeability and average protection against microbial corrosion, making it difficult to effectively protect the corrosion of marine building steel structures.

Method used

It is provided with a metal surface rust-resistant coating, which contains 20% to 50% of the reactive diluent, 10% to 30% of the epoxy resin, 4% to 10% of zinc phosphate, 2% to 10% of the tannic acid, 0.2% to 0.6% of the nanocarbon secondary doped polyaniline composite material and 0.1% to 5% of the long-acting rust converter, which can be directly coated on the rusted metal surface to form a dense conversion film and prevent the infiltration of corrosive media.

Benefits of technology

The coating has high permeability and high rust conversion efficiency, can form an effective protective layer, extend the service life of the steel structure to more than 20 years, reduce maintenance frequency, save resources, manpower and material resources, and has significant economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552558A_ABST
    Figure CN119552558A_ABST
Patent Text Reader

Abstract

The invention provides a metal surface rusty anticorrosive paint, and relates to the related technical field of marine metal surface rust prevention and conversion, when the addition amount of a nanocarbon secondary doped polyaniline composite material is in a proportion range of 0.2%-0.6%, the anticorrosive capability of a coating is remarkably improved, the distribution density of the nanocarbon secondary doped polyaniline composite material in the coating is increased, and the corrosion resistance of the coating is improved. The polyaniline composite material can form a conductive path to accommodate electrons transferred by a metal matrix and enhance the shielding effect of the coating, and meanwhile, the polyaniline composite material can make up the defects of the coating and prevent a corrosion medium from permeating the coating along gaps, so that the coating is prevented from being damaged to lose the protection capability on the metal matrix; tannic acid, gallic acid and salicylic acid are simultaneously adopted in the long-acting rust transforming agent and are matched with one another, so that the tannic acid, gallic acid and salicylic acid can form a firm complex layer with formed metal oxide or metal through chelation, and the synergistic migration protection effect is enhanced; and a relatively compact and flat conversion film can be formed on the rusted metal surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to rust prevention and rust conversion of marine metal surfaces, and in particular to a rust-proof anti-corrosion coating for metal surfaces. Background Art

[0002] Marine building steel structure refers to large structures built in the marine environment using steel as the main building material, such as offshore platforms, cross-sea bridges, offshore wind power generation facilities, etc. Among them, marine building steel structure has the characteristics of light weight, high strength, good plasticity, etc. It can be designed into various complex shapes and structures according to the actual environment and work requirements, and withstand various complex loads in the marine environment (such as waves, tides, storms, etc.); at the same time, compared with traditional building materials, it is easy to process and install, which can greatly shorten the construction period of marine buildings, and is therefore widely used in marine buildings.

[0003] The corrosion factors of marine steel structures in the marine environment are complex and diverse, mainly including chloride ions in seawater, salt in the marine atmosphere, microorganisms, acid rain, direct sunlight, and temperature changes between day and night. These factors will cause different degrees of corrosion of marine steel structures, which will affect the safety and service life of marine steel structures. Among them, seawater contains a large amount of chloride ions, which will react with iron oxide on the surface of marine steel structures to form soluble chlorides, accelerating the corrosion of marine steel structures. At the same time, the marine atmospheric environment is characterized by high salinity and high humidity, which will cause a layer of water film to form on the surface of the steel structure, providing a basic environment for electrochemical corrosion, and will also accelerate the corrosion of marine steel structures; especially in projects such as marine wind power generation, marine steel structures are exposed to the marine environment for a long time, and the corrosion problem is prominent. Microbial corrosion of marine steel structures, specifically various microorganisms in the marine environment, will adhere to the surface of the steel structure and produce acidic substances to corrode the marine steel structure; microbial corrosion usually causes small pore-shaped corrosion pits on the surface of marine steel structures, seriously affecting their strength and stability, and further aggravating the electrochemical corrosion of marine steel structures. Furthermore, acid rain, direct sunlight, and temperature changes between day and night will also aggravate the corrosion of marine steel structures. Compared with non-marine environments, the corrosion rate of steel structures in marine environments is several times that of non-marine environments. The corrosion inhibition and maintenance of marine steel structures requires a lot of manpower and material resources.

[0004] The most economical, effective and simplest way to prevent corrosion on the surface of marine steel structures is to apply an anti-corrosion coating on the surface. In order to enhance the performance and effect of anti-corrosion, it is necessary to thoroughly remove the rust on the substrate and expose the metallic luster on the steel surface. The main purpose of coating is to protect metal materials from corrosion, extend the service life of equipment, reduce maintenance costs, and prevent safety accidents caused by structural damage. However, before coating, traditional anti-corrosion coatings need to be strictly treated on the metal substrate, and the process requirements are harsh, which not only increases the maintenance cost, but also causes damage to the equipment structure. Adding a rust converter with the effect of converting rust layer to the coating allows it to be directly coated on a metal substrate with a certain rust surface, achieving both rust conversion and rust prevention. This rust-resistant coating can be applied to various metal equipment and has good use value.

[0005] At present, the widely used rust removal methods include mechanical methods, sandblasting, flame and chemical methods, but these methods have the defects of high labor intensity, low labor efficiency, high cost, environmental pollution, health hazards to construction personnel, etc., especially in the in-service engineering structure facilities, the components are complex, the environment is special, and the construction of conventional rust removal methods is difficult. Therefore, in order to reduce labor intensity, enhance and improve the anti-corrosion effect, enhance the adhesion of the coating on the surface of the steel substrate, save resources, and achieve environmental protection, high efficiency, energy saving, and low surface treatment, it is urgent to provide a technology that can directly convert rust into a steel protective film, and then the anti-rust coating can be directly applied to the rusty metal surface to stabilize, passivate or convert the rusted surface, and convert the rust into a stable and harmless substance, without strict rust removal and surface treatment, low production cost, high rust conversion rate, and high anti-corrosion performance. Summary of the invention

[0006] The present invention aims at the shortcomings of existing rust-proof and rust-converting agents, such as high toxicity, poor construction economy, poor permeability and general protection effect against microbial corrosion, and provides a rust-proof coating for metal surfaces. The coating is suitable for steel structures, especially for connection parts of steel structures, has good permeability and high rust conversion efficiency, can form a relatively dense and smooth conversion film, and the formed conversion film can effectively prevent corrosive media from penetrating into and contacting the metal, can convert harmful rust into a protective layer that is beneficial to corrosion prevention, and provide effective protection for the metal substrate. The anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits.

[0007] The invention provides a rust-proof coating for metal surface, comprising 20% ​​to 50% by mass of an active diluent, 10% to 30% by mass of an epoxy resin, 4% to 10% by mass of zinc phosphate, 2% to 10% by mass of tannic acid, 0.2% to 0.6% by mass of a nano-carbon secondary doped polyaniline composite material and 0.1% to 5% by mass of a long-acting rust conversion agent, wherein the nano-carbon secondary doped polyaniline composite material is composited by secondary doping of polyaniline with a mass ratio of 15 to 25:1:15 to 25 of aniline, graphene and carbon nanotubes.

[0008] Optionally, the long-acting rust conversion agent includes 30% to 50% by mass of carrier oil, 1% to 4% by mass of osmotic stabilizer, 6% to 10% by mass of sustained-release carrier, 3% to 5% by mass of sterilizer, 1% to 2% by mass of antioxidant, 2% to 6% by mass of thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent is 25% to 50%.

[0009] Optionally, the mass percentage of tannic acid contained in the long-acting rust conversion agent is 13% to 15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent is 11% to 12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent is 10% to 15%.

[0010] Optionally, the mass percentage of tannic acid contained in the long-acting rust conversion agent is 14%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent is 13%.

[0011] Optionally, the nanocarbon secondary doped polyaniline composite material is prepared by the following method:

[0012] (1) taking two equal volumes of 1 mol / L doping acid solutions, respectively adding aniline-graphene mixture and ammonium persulfate, wherein the molar ratio of the aniline-graphene mixture to the ammonium persulfate is 0.8:1, and uniformly mixing the two with a magnetic stirrer for 1 to 2 hours, placing them at room temperature and letting them stand for 20 to 26 hours, washing the obtained product with ethanol and deionized water successively until neutral, and obtaining a primary doped polyaniline-graphene composite material after drying and grinding; wherein the mass ratio of aniline to graphene in the aniline-graphene mixture is 15 to 25:1;

[0013] (2) adding excess ammonia water to the primary doped polyaniline-graphene composite material for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 20 to 26 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-graphene composite material;

[0014] (3) taking two equal volumes of 1 mol / L doped acid solutions, respectively adding aniline-carbon nanotube mixture and ammonium persulfate, wherein the molar ratio of the aniline-carbon nanotube mixture to the ammonium persulfate is 0.8:1, and uniformly mixing the two with a magnetic stirrer for 1 to 2 hours, placing them at room temperature and letting them stand for 20 to 26 hours, washing the obtained product with ethanol and deionized water successively until neutral, and obtaining a primary doped polyaniline-carbon nanotube composite material after drying and grinding; wherein the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture is 15 to 25:1;

[0015] (4) adding excess ammonia water to the primary doped polyaniline-carbon nanotube composite material for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 20 to 26 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-carbon nanotube composite material;

[0016] (5) The intrinsic polyaniline-graphene composite material and the intrinsic polyaniline-carbon nanotube composite material were added to a 1 mol / L doped acid solution in a mass ratio of 1:1, mixed and stirred, and then allowed to stand for 20 to 26 hours. After that, they were filtered and washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain the nanocarbon secondary doped polyaniline composite material.

[0017] Optionally, the mass ratio of aniline to graphene in the aniline-graphene mixture is 20:1, and the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture is 20:1.

[0018] Optionally, the mass percentage of the nano-carbon secondary doped polyaniline composite material included in the metal surface rust anti-corrosion coating is 0.3% to 0.6%.

[0019] Optionally, the mass percentage of the nano-carbon secondary doped polyaniline composite material included in the metal surface rust anti-corrosion coating is 0.5%.

[0020] Optionally, the metal surface rust anti-corrosion coating includes a long-acting rust conversion agent in an amount of 3% by mass.

[0021] The present invention has the following beneficial technical effects:

[0022] The invention provides a metal surface rust anticorrosion coating in which the addition mass percentage of a nano-carbon secondary doped polyaniline composite material is 0.2% to 0.6%. When the addition amount of the nano-carbon secondary doped polyaniline composite material is less than the range, the effect that can be exerted is limited, and the over-dispersion leads to failure to form a complete conductive path in the coating, which is not conducive to forming a passivation film, so the anticorrosion effect of the coating is not significantly improved; when the addition amount of the nano-carbon secondary doped polyaniline composite material is within the ratio range, the anticorrosion ability of the coating is significantly improved, the distribution density of the nano-carbon secondary doped polyaniline composite material in the coating is increased, a conductive path can be formed to accommodate electrons transferred from a metal matrix, and the shielding effect of the coating is enhanced. At the same time, the polyaniline composite material can also make up for coating defects, block corrosive media from penetrating the coating along gaps, and prevent the coating from being damaged and losing its protective ability to the metal matrix. The long-acting rust converter uses tannic acid, gallic acid and salicylic acid at the same time. Tannic acid, gallic acid and salicylic acid can cooperate with each other to form a strong complex layer with the already formed metal oxide or the metal itself through chelation. The synergistic effect of the three corrosion inhibitors, tannic acid, gallic acid and salicylic acid, enhances the synergistic migration protection effect, and can form a relatively dense and smooth conversion film on the surface of the rusted metal. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal. It is suitable for steel structures, especially for steel structure connection parts. It has good permeability and high rust conversion efficiency. It can convert harmful rust into a protective layer that is beneficial to corrosion prevention, provide effective protection for the metal matrix, and the anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 are metallographic images of different transformation products of the embodiments of the present invention;

[0025] Figure 2 Schematic diagram of scanning electron microscopy of different transformation products of the embodiments of the present invention;

[0026] Figure 3 The Nyquist diagram and Bode diagram of the coating of the bare steel sample with different immersion times according to the embodiment of the present invention are shown;

[0027] Figure 4 The impedance spectrum equivalent circuit diagram of an embodiment of the present invention;

[0028] Figure 5 The Nyquist diagram and Bode diagram of the rusted steel sample coating at different immersion times according to the embodiment of the present invention are shown;

[0029] Figure 6 The impedance value comparison between the rusted steel sample coating and the bare steel sample coating in the embodiment of the present invention;

[0030] Figure 7 This is a salt spray test diagram based on a bare steel sample coating for 1440 hours according to an embodiment of the present invention;

[0031] Figure 8 This is a salt spray test diagram based on a rusted steel coating for 1440 hours according to an embodiment of the present invention;

[0032] Fig. 9 This is a salt spray test diagram based on a bare steel sample coating for 1440 hours according to an embodiment of the present invention;

[0033] Fig.10 This is a salt spray test diagram based on a rusted steel coating for 1440 hours according to an embodiment of the present invention;

[0034] Fig.11 The Nyquist diagram and Bode diagram of the rust-proof coating on the metal surface according to the embodiment of the present invention based on the bare steel sample coating at different immersion times;

[0035] Fig.12 The Nyquist diagram and Bode diagram of the rust-resistant coating on metal surface according to the embodiment of the present invention based on different immersion times of the rust-resistant steel coating;

[0036] Fig.13 This is a comparative analysis diagram of the AC impedance of the rust-resistant coating on the metal surface according to an embodiment of the present invention;

[0037] Fig.14 This is a salt spray test diagram of the metal surface rust-proof coating based on the bare steel sample coating for 1440 hours according to the embodiment of the present invention.

[0038] Fig.15 The salt spray test diagram of the metal surface rust-proof coating based on the rusted steel coating for 1440 hours according to the embodiment of the present invention is shown in FIG. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In view of the shortcomings of existing anti-rust and rust-converting coatings, such as high toxicity, poor construction economy, poor permeability, and general protection effect against microbial corrosion, the embodiments of the present invention provide a rust-proof coating for metal surfaces, which is suitable for steel structures, especially for steel structure connection parts. It has good permeability and high rust conversion efficiency, and can form a relatively dense and smooth conversion film. The formed conversion film can effectively prevent corrosive media from penetrating into and contacting the metal, and can convert harmful rust into a protective layer that is beneficial to corrosion prevention, thereby providing effective protection for the metal substrate. The anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits.

[0041] A rust-proof coating for metal surfaces provided by an embodiment of the present invention comprises 20% to 50% by mass of an active diluent, 10% to 30% by mass of an epoxy resin, 4% to 10% by mass of zinc phosphate, 2% to 10% by mass of tannic acid, 0.2% to 0.6% by mass of a nano-carbon secondary doped polyaniline composite material, and 0.1% to 5% by mass of a long-acting rust converter, wherein the nano-carbon secondary doped polyaniline composite material is composited by secondary doping of polyaniline with a mass ratio of 15 to 25:1:15 to 25 of aniline, graphene and carbon nanotubes.

[0042] Furthermore, a long-acting rust conversion agent used in a rust-proof coating for metal surfaces provided in an embodiment of the present invention comprises 30% to 50% by mass of a carrier oil, 1% to 4% by mass of a penetration stabilizer, 6% to 10% by mass of a sustained-release carrier, 3% to 5% by mass of a bactericidal agent, 1% to 2% by mass of an antioxidant, 2% to 6% by mass of a thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent is 25% to 50%.

[0043] Among them, the mass percentage of tannic acid contained in the long-acting rust converter used in the embodiment of the present invention is 12% to 16%, the mass percentage of salicylic acid contained in the long-acting rust converter is 10% to 13%, and the mass percentage of gallic acid contained in the long-acting rust converter is 8% to 18%. Tannic acid, gallic acid and salicylic acid at this mass percentage can cooperate with the formed metal oxide or the metal itself to form a firm complex layer through chelation, and the three corrosion inhibitors of tannic acid, gallic acid and salicylic acid can better play a synergistic role, enhance the role of synergistic migration protection, and form a relatively dense and smooth conversion film on the surface of the corroded metal. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal.

[0044] Furthermore, the mass percentage of tannic acid contained in the long-acting rust conversion agent of the embodiment of the present invention is 13% to 15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent is 11% to 12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent is 10% to 15%.

[0045] Rust converters prepared from different acids react differently with rust. Tannic acid contains a large number of hydroxyl and carboxyl groups, which can react with iron ions in the rust layer to form a stable tannic acid iron complex salt; gallic acid contains one carboxyl group and three phenolic hydroxyl groups, of which the phenolic hydroxyl group has a strong chelating ability and can form a complex with iron ions; salicylic acid reacts relatively mildly with rust, and can react chemically with rust at room temperature or high temperature to form a harmless chelate with a certain protective effect. However, due to the difference in acidity, the conversion effect of different acids on the rust layer and the degree of damage to the matrix are different. Strong acidic substances will corrode the metal matrix, and the excess hydrogen produced will also lead to an increase in paint film defects. Therefore, even if a protective layer is formed on the metal surface, it will quickly fail and cannot achieve the purpose of long-term corrosion protection. Weakly acidic substances cannot provide enough anions to react with iron ions, so they cannot form stable chelates to protect the matrix, and the residual rust will continue to expand, causing the metal corrosion to worsen. Tannic acid, gallic acid and salicylic acid are combined to prepare a composite rust conversion agent, which is then applied to rusty steel samples. This can make up for the defects caused by a single acid and give full play to the synergistic advantages of their mutual cooperation.

[0046] The process of the reaction between the rust conversion agent and the rust layer on the metal surface can be divided into the following three stages: first, the acidic substance is hydrolyzed to release hydrogen ions; second, the hydrogen ions react with the rust on the metal surface to dissolve it into iron ions or ferrous ions; finally, the generated acid radical ions chelate with the generated ionic iron to convert into a stable and harmless organic chelate. Among the three substances, tannic acid, gallic acid and salicylic acid, tannic acid has a stronger acidity and is a medium-strong organic acid, which can easily dissociate water molecules. Therefore, adding tannic acid first can promote the hydrolysis process, and while generating anions, a large amount of hydrogen ions are precipitated (refer to formula (1)), providing a favorable condition for the subsequent reaction with rust. Salicylic acid is slightly soluble in water, but has a high complexing strength with iron ions. In a tannic acid environment, hydrogen ions can react with rust to form ionic iron (see formula (2)). Under this condition, salicylic acid is more likely to complex with free iron ions to form a stable and harmless precipitate. This substance can firmly adhere to the metal surface to form a complex precipitation layer. Therefore, adding an appropriate amount of salicylic acid after adding tannic acid can not only slow down the corrosion rate, but also improve the protection of the metal matrix. Tannic acid can also play a role in this stage. After hydrolysis, under the action of its many polar groups, it can react with iron ions or ferrous ions to form a blue-black complex (see formula (3)). Tannic acid also has the characteristic of absorbing oxygen, which can prevent metal oxidation and improve its passivation ability. Gallic acid is a small molecule polyphenol compound with weaker activity. It can also react with rust when used alone to convert it into stable and harmless compounds, but the process is slow and cannot achieve the purpose of rapid rust removal and cannot inhibit further development of rust. However, it is environmentally friendly and does not easily corrode the metal matrix. Therefore, after adding tannic acid and salicylic acid, adding an appropriate amount of gallic acid can replace part of the organic medium and strong acid, reduce the overall acid strength, achieve rapid conversion of the rust layer, and prevent corrosion to the metal matrix.

[0047] R-OH→RO - +H + (1)

[0048] 5H + +FeOOH+Fe(OH)2→Fe 3+ +Fe 2+ +4H2O (2)

[0049] 5R-O - +Fe 2+ +Fe 3+ →Fe(RO)3↓+Fe(RO)2↓ (3)

[0050] Through a large number of experimental studies, it was found that when the mass percentage of tannic acid contained in the long-acting rust converter of the embodiment of the present invention is 14%, the mass percentage of salicylic acid contained in the long-acting rust converter is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust converter is 13%, the tannic acid, gallic acid and salicylic acid at this mass percentage can cooperate with the already formed metal oxide or the metal itself to form a firm complex layer through chelation, and the three corrosion inhibitors of 14% tannic acid, 11.5% gallic acid and 13% salicylic acid can better play a synergistic role, enhance the synergistic migration protection effect, and can form a relatively dense and smooth conversion film on the surface of the rusted metal. The conversion film formed at this mass percentage has the least surface cracks and a shallower depth, and the formed conversion film can better hinder the corrosive medium from penetrating and contacting the metal.

[0051] The carrier oil used in the long-acting rust conversion agent of the embodiment of the present invention is at least one of poly-α-olefin oil, polybutene, synthetic cycloalkane, vegetable oil-based polyol ester, and polyether. The osmotic stabilizer is a mixture of soybean lecithin and Tween-60 in a weight ratio of 2:1. The sustained-release carrier is a mixture of sepiolite powder and diatomaceous earth in a weight ratio of 2:1. The sterilizer is a mixture of fluopicolide, pyraclostrobin and triazole sterilizer in a weight ratio of 1:1:1. The antioxidant is a mixture of antioxidant 1010 and antioxidant BHT in a weight ratio of 3:1.

[0052] A long-acting rust converter according to an embodiment of the present invention has a low surface treatment requirement and is suitable for port and terminal facilities, offshore platforms, power plant steel frames, storage tank bottom edge plates, and pipeline valves in the marine industry. Usually, due to the limitations of operating conditions and the like at the construction site, it is difficult to achieve the required level of surface treatment. However, when a long-acting rust converter according to an embodiment of the present invention is used, the surface treatment only needs to reach St2.0, and the construction process is flexible and simple, and the construction tolerance is good. In view of the characteristics of the metal structure, a variety of construction methods can be used, including manual smearing, scraping, brushing, glue gun extrusion application, and spraying; in addition, a long-acting rust converter according to an embodiment of the present invention can be constructed with water and rust, and the anti-corrosion protective film formed after coating can easily cover the surface of the object to be protected.

[0053] A long-acting rust conversion agent according to an embodiment of the present invention has a long-lasting anti-corrosion protection function, the anti-corrosion layer has strong adhesion and good dense isolation, outstanding synergistic protection, good permeability and strong chelating rust inhibition ability. First, a long-acting rust conversion agent according to an embodiment of the present invention uses tannic acid, gallic acid and salicylic acid, which can form a firm complex layer with the already formed metal oxide or the metal itself through chelation. The three corrosion inhibitors of tannic acid, gallic acid and salicylic acid cooperate with each other to play a synergistic role, thereby enhancing the synergistic migration protection effect; secondly, a long-acting rust conversion agent according to an embodiment of the present invention uses two antioxidants to work synergistically, which can effectively prevent the anti-corrosion layer from acidification and oxidative deterioration for a long time, thereby ensuring the long-term effectiveness of the anti-corrosion effect of the anti-corrosion layer. A long-acting rust conversion agent in an embodiment of the present invention adopts a combination of three bactericides, namely, fluopicolide, pyraclostrobin and triazoles, which can effectively inhibit or kill microorganisms that are prone to growth, such as sulfate-reducing bacteria, sulfur-oxidizing bacteria, saprophytes, iron bacteria and fungi, thereby preventing corrosion damage caused by the failure of anti-corrosion materials due to the secretion of intermediate products and / or final products of microbial cell metabolism and exoenzymes.

[0054] In the embodiment of the present invention, Q235 low-carbon steel, which is commonly used in engineering projects, is selected as a test substrate for metal surface anti-rust conversion. A rust layer with good bonding strength is prepared through continuous salt spray exposure. Different rust conversion agents are added to epoxy resin to prepare a coating, which is then applied to a rusted steel sample and a bare steel sample that have been uniformly treated.

[0055] In order to make the rust adhere better to the substrate surface, the Q235 low carbon steel working electrode (10mm×10mm×10mm) and the Q235 low carbon steel sample (150mm×75mm×1mm) were degreased and dusted, and polished step by step with 400 mesh, 800 mesh, and 1000 mesh sandpaper respectively. Finally, the surface was wiped with anhydrous ethanol to clean it, and put it into the salt spray box for accelerated corrosion for 72h. The steel surface was completely attached by the rust layer, and it was taken out and dried naturally in the air. The surface rust was removed with sandpaper and a soft brush, and the residual NaCl in the rust layer was rinsed with deionized water. The oven temperature was set to 35℃, and the rust layer of (37±4.2)μm was obtained after drying for 24h.

[0056] Use an electronic balance to weigh a certain amount of epoxy resin and add it to a laboratory disperser. Add an active diluent and disperse it evenly at a speed of 1500r / min for 5 minutes. Then mix the filler, rust converter, dispersant and epoxy resin. The amount of rust converter added is 4wt.%, and the ratio of the volume fraction of pigments and fillers to the critical volume fraction of pigments and fillers is fixed at 0.7. Adjust the speed to 2000r / min and stir for 5 minutes, then add the additive and continue stirring for 1 hour to make it evenly dispersed. After cooling, put it into a bottle and label it for later use.

[0057] The long-acting rust converter of the embodiment of the present invention and the rust converter of the comparative example were respectively applied to the treated substrate surface by brushing, (480±30)μm, dried at room temperature for 7 days, and after being completely cured, the basic performance test, AC impedance test and neutral salt spray test of the coating were carried out. Among them, the comparative examples are rust converters prepared by using tannic acid and salicylic acid as corrosion inhibitors, tannic acid as corrosion inhibitor, salicylic acid as corrosion inhibitor, and gallic acid as corrosion inhibitor. The product morphology of the basic performance test is as follows Figure 1 As shown, Figure 1 The image is obtained by observing the surface of the rust layer after being converted by different rust conversion agents using a metallographic microscope, with a magnification of 400 times. Figure 1 a is rusty steel; Figure 1 b is a composite acid system of tannic acid, gallic acid and salicylic acid; Figure 1 c is a composite acid system of tannic acid and salicylic acid; Figure 1 d is tannic acid; Figure 1 e is salicylic acid; Figure 1 f is gallic acid. Figure 1 It can be seen that the rust layer surface after being treated with different rust conversion agents presents different states. Among them, the tannic acid, gallic acid and salicylic acid composite acid system ( Figure 1 b) has the best conversion effect. Figure 1 Compared with the rusted steel sample shown in a, the original rust morphology on the surface was transformed to form a relatively complete and dense conversion film. Tannic acid and salicylic acid composite acid system ( Figure 1 c) The rust layer also undergoes transformation and forms a conversion film on the surface, but there are some holes and small cracks on the surface of the film. Figure 1 d) Salicylic acid ( Figure 1 e) and gallic acid ( Figure 1 f) It also has a certain transformation effect. You can see that the rust on the original rust layer disappears, but the surface after transformation is rough and uneven, which means that the rust layer transformation is incomplete and there may be residual rust.

[0058] The film formed before and after the rust layer transformation was characterized by scanning electron microscopy. Figure 2 As shown, Figure 2 a is rusty steel; Figure 2 b is gallic acid; Figure 2 c is salicylic acid; Figure 2 d is tannic acid; Figure 2 e is a composite acid system of tannic acid and salicylic acid; Figure 2 f is a composite acid system of tannic acid, gallic acid and salicylic acid. Figure 2It can be seen from a that the surface of the unconverted rusted steel sample presents blocky and granular morphology, and the rust layer is loose with a large number of pores, which will destroy the structure of the metal matrix and affect its performance. After the rusted steel sample is treated with different rust conversion agents, it can be found that the surface morphology has obvious changes. Among them, the rust layer on the sample is treated with gallic acid ( Figure 2 b) and salicylic acid ( Figure 2 c), the block structure basically disappeared, and a relatively dense conversion film was formed, but there were still obvious cracks on the surface of the film layer, and some granular products were distributed, especially the film layer obtained by salicylic acid conversion was rougher, because the rust was not completely converted and still remained on the surface of the film layer. Figure 2 d), the morphology of the rusted steel samples after conversion has been greatly improved. Although there are still cracks on the surface, the loose rust has completely disappeared and has been converted into a dense and smooth conversion film, which has a certain protective effect on the metal substrate. However, the film layer after conversion by tannic acid has relatively more cracks and the gap width is larger; after conversion by tannic acid and salicylic acid composite acid system ( Figure 2 After treatment with tannic acid, gallic acid, and salicylic acid composite acid system ( Figure 2 f) after treatment, the smoothness and flatness of the conversion film formed are slightly lower, but the cracks on the surface are fewer and shallower, and no metal matrix is ​​exposed, which can effectively inhibit the penetration of corrosive media.

[0059] Based on the analysis of the AC impedance results of the bare steel sample coating, Figure 3 As shown, the equivalent circuit diagram of the impedance spectrum based on the bare steel sample coating is shown in Figure 4 As shown, Figure 4 Where Rs represents the solution resistance, Qc represents the coating capacitance, Rp represents the coating resistance, Rc is the micropore resistance of the electrolyte penetrating coating, Qdl and Rt represent the double layer capacitance and charge transfer resistance at the interface between metal and coating, respectively. Figure 4 The equivalent circuit diagram with only one time constant is fitted as shown in a. As the immersion time increases, the corrosive medium penetrates the coating and contacts the metal, and corrosion occurs. The impedance arc diffusion phenomenon becomes obvious from the Nyquist diagram. At this time, according to Figure 4 The equivalent circuit with two time constants shown in b is fitted.

[0060] refer to Figure 3 As shown in the figure, the larger the impedance arc radius of the Nyquist diagram, the better the coating's ability to block corrosive media. Similarly, the higher the impedance modulus value in the low-frequency region of the Bode diagram, the stronger the coating's anti-corrosion ability. Figure 3It can be seen from Table 1 that during the entire immersion process, the impedance arc radius of each coating in the Nyquist diagram gradually decreases, the impedance value decreases, and the low-frequency 0.01Hz impedance modulus in the Bode diagram also shows a downward trend. This is because as the immersion time increases, the corrosive medium gradually penetrates into the coating, weakening its shielding ability, thereby reducing the coating's ability to protect the metal substrate. Analysis shows that compared with 24h( Fig.10 Compared with the case of immersion for 360h ( Figure 3 The impedance values ​​of the coatings decreased after the addition of the coatings, but were all higher than 1010Ω·cm 2 This indicates that the coating containing the rust conversion agent has a certain anti-corrosion ability and can effectively inhibit the penetration of corrosive media. After immersion for 1440 hours, Figure 3 As shown in Figures e1 and e2, the impedance modulus of the coating prepared by gallic acid at 0.01Hz is lower than 108Ω·cm 2 , and the impedance arc diffuses in the low-frequency region, indicating that the corrosive medium has penetrated the coating and reacted with the metal matrix to cause corrosion, causing the coating to gradually lose its ability to protect the metal matrix. The impedance value of the coating prepared by tannic acid, salicylic acid and its composite acid system is still higher than 1010Ω·cm 2 , and the impedance arc radius and low-frequency impedance modulus of these three coatings are significantly higher than those of other coatings during the entire immersion period.

[0061] Table 1 AC impedance fitting results based on different immersion time of bare steel sample coating

[0062]

[0063] Based on the AC impedance analysis of the rusted steel sample coating, Figure 5 As shown, the equivalent circuit diagram of the impedance spectrum based on the rusted steel sample coating is as follows Figure 5 As shown, from Figure 5 It can be seen from Table 2 that during the entire immersion process, the impedance arcs in the Nyquist diagrams of all coatings gradually become complete, indicating that the failure modes of each coating are basically the same, and the corrosive medium gradually penetrates into the coating as the immersion time increases. Figure 5 It can be seen from Figures a1 and a2 that after immersion for 24 hours, the impedance arc radius of each coating in the Nyquist diagram is relatively large, and the low-frequency impedance modulus values ​​of the Bode diagram are all higher than 1010Ω·cm 2 , at this time, each coating has a good shielding effect. After immersion for 360 hours, if Figure 5 As shown in Figures b1 and b2 of the figure, the impedance arc radius in the Nyquist diagram has decreased, and the impedance modulus in the Bode diagram has also begun to decrease, but overall there is little difference compared to the 24h state, and it is still in the early stage of immersion. Figure 5After the Nyquist diagram and the Bode diagram have changed significantly, it can be seen from Table 2 that the impedance values ​​of the sample coatings prepared by gallic acid and salicylic acid have been greatly reduced, indicating that the metal substrate has been corroded by corrosion products. The reason is that the porosity of these two coatings is large and the shielding ability is poor, which leads to the penetration of corrosive media, resulting in a rapid decrease in electrochemical impedance values. Continue to immerse the coating, it can be found that the radius of the Nyquist impedance arc is further reduced, and a platform appears in the low-frequency region of the impedance modulus curve of the Bode diagram, indicating that each coating has infiltrated by corrosive media and the shielding ability of the coating has decreased. When the immersion time reaches 1440h, each coating has basically formed a complete impedance arc. The coating prepared by the composite acid system of tannic acid, gallic acid, and salicylic acid has decreased relatively slowly, indicating that the conversion film of the composite acid system coating has played a barrier role, slowing down the process of the electrolyte solution penetrating into the coating and limiting the corrosion behavior.

[0064] Table 2 AC impedance fitting results based on different immersion time of rusted steel sample coating

[0065]

[0066] The changes of the AC impedance fitting results of different coatings and different samples with immersion time are plotted as a bar graph, such as Figure 6 As shown, Figure 6 a is a composite acid system of tannic acid, salicylic acid and gallic acid; Figure 6 b is a composite acid system of tannic acid and salicylic acid; Figure 6 c is tannic acid; Figure 6 d is salicylic acid; Figure 6 e is gallic acid. Figure 6 It can be seen that the impedance values ​​of all coatings, whether based on bare steel or rusted steel, decrease with the increase of immersion time, but the impedance value of the rusted steel coating is always higher than that of the bare steel, especially the tannic acid, salicylic acid, gallic acid composite acid system ( Figure 6 The coating prepared as shown in a) has an impedance value improvement rate of about 30%. This is because the rust conversion agent in the coating plays a role and reacts with the rust layer on the sample to form a conversion film, which inhibits the penetration of corrosive media and strengthens the protection of the metal substrate.

[0067] Figure 7 and Figure 8 The results are as follows: the coatings prepared by different rust conversion agents were coated on bare steel samples and rusted steel samples, respectively, after 1440 hours of neutral salt spray test. Figure 7 a and Figure 8 a is a composite acid system of tannic acid, salicylic acid and gallic acid; Figure 7 b and Figure 8 b is a composite acid system of tannic acid and salicylic acid; Figure 7 c and Figure 8 c is tannic acid; Figure 7 d and Figure 8 d is salicylic acid; Figure 7 e and Figure 8 e is gallic acid. Figure 7 and Figure 8 It can be seen that different rust converters have different corrosion degrees, and the same converter coating applied on samples in different states will also have different corrosion conditions. Figure 7 It can be seen that the coating prepared by the composite acid system of tannic acid, salicylic acid and gallic acid has a lighter overall corrosion degree than other coatings. There is almost no change in the scratch-free area of ​​the upper half of the sample, and only a small amount of rust is generated in the scratched area of ​​the lower half, indicating that the coating can play a role in shielding the corrosive medium. Figure 8 The corrosion of the coating on the rusted steel sample shown is lighter, and the degree of corrosion in the scratched area is less than that of the bare steel sample, achieving the effect of converting the rust layer to protect the metal substrate; the corrosion of the coating prepared by salicylic acid and gallic acid is more serious, especially for the rusted steel sample. Not only is the bulge phenomenon obvious at the scratched area, but also bubbles appear in the upper area without scratches, which creates a gap between the coating and the metal substrate. The reason for this is that on the one hand, the barrier ability of the coating itself is poor, and the corrosive medium easily penetrates the coating and contacts the metal substrate, producing a large amount of corrosion products, resulting in volume expansion. On the other hand, the coating cannot convert the rust on the sample well, causing it to spread and diffuse, thereby greatly reducing the impedance of the coating. The results of the salt spray test are consistent with the results of the AC impedance. The fewer the bubbling phenomenon and corrosion products of the sample coating, the higher the impedance value of the coating, and the better the anti-corrosion effect.

[0068] Fig. 9 and Fig.10 The results of neutral salt spray tests on bare steel samples and rusted steel samples were performed on coatings prepared by rust conversion agents of composite acid systems of tannic acid, salicylic acid and gallic acid with different weight ratios. Fig. 9 a and Fig.10 a is tannic acid: salicylic acid: gallic acid = 3:2:1; Fig. 9 b and Fig.10 b is tannic acid: salicylic acid: gallic acid = 2:1:1; Fig. 9 c and Fig.10 c is tannic acid: salicylic acid: gallic acid = 1:2:1; Fig. 9 d and Fig.10 d is tannic acid: salicylic acid: gallic acid = 1:1:1; Fig. 9 e and Fig.10e is tannic acid: salicylic acid: gallic acid = 1:1:2. It can be seen that after 1440h of testing in the salt spray test chamber, the coatings all have different degrees of corrosion, among which the long-acting rust converter of the embodiment of the present invention with a mass percentage ratio of tannic acid: salicylic acid: gallic acid = 1:1:2 in the composite acid system has relatively serious corrosion, with more rust products near the scratches, especially the coating of the bare steel sample has bubbling. The surface state of the coatings with other additions is relatively good, especially the coating with a ratio of tannic acid: salicylic acid: gallic acid = 3:2:1 in the composite acid system, which has almost no signs of corrosion.

[0069] Through the above product morphology and electrochemical performance analysis, the following conclusions are drawn:

[0070] (1) In the comparative analysis of the rust conversion system, it can be seen that the rust on the surface of the sample after conversion by the composite acid system of tannic acid, gallic acid and salicylic acid disappears, and a relatively dense and smooth conversion film is formed. Although there are some small cracks, no metal matrix is ​​exposed, indicating that the composite acid system rust converter reacts with the rust layer on the surface of the sample and has good rust conversion performance. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal.

[0071] (2) Through the AC impedance test and the neutral salt spray test, it can be found that the coating with the composite acid system of tannic acid, gallic acid and salicylic acid has a certain ability to turn rust on rusted steel samples, and can also play an anti-corrosion role on bare steel samples. After 1440 hours of immersion in 3.5wt.% NaCl solution, the coating on the rusted steel sample and the bare steel sample can still maintain a resistance of 1010Ω·cm 2 The above results show that the impedance value of the rusted steel sample coating is higher than that of the bare steel sample coating; after 1440 hours of neutral salt spray test, the coating prepared by the tannic acid, gallic acid, salicylic acid composite acid system (tannic acid: salicylic acid: gallic acid = 3:2:1) has only a small amount of rust at the scratches, without bubbling, shedding, etc. This shows that the coating prepared by the rust conversion agent of the embodiment of the present invention can convert harmful rust into a protective layer that is beneficial to corrosion protection, providing effective protection for the metal substrate.

[0072] The nano-carbon secondary doped polyaniline composite material used in the metal surface rust anti-corrosion coating of the embodiment of the present invention is prepared by the following method:

[0073] (1) taking two equal volumes of 1 mol / L doping acid solutions, respectively adding aniline-graphene mixture and ammonium persulfate, wherein the molar ratio of the aniline-graphene mixture to the ammonium persulfate is 0.8:1, and uniformly mixing the two with a magnetic stirrer for 1 to 2 hours, placing them at room temperature and letting them stand for 20 to 26 hours, washing the obtained product with ethanol and deionized water successively until neutral, and obtaining a primary doped polyaniline-graphene composite material after drying and grinding; wherein the mass ratio of aniline to graphene in the aniline-graphene mixture is 15 to 25:1;

[0074] (2) adding excess ammonia water to the primary doped polyaniline-graphene composite material for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 20 to 26 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-graphene composite material;

[0075] (3) taking two equal volumes of 1 mol / L doped acid solutions, respectively adding aniline-carbon nanotube mixture and ammonium persulfate, wherein the molar ratio of the aniline-carbon nanotube mixture to the ammonium persulfate is 0.8:1, and uniformly mixing the two with a magnetic stirrer for 1 to 2 hours, placing them at room temperature and letting them stand for 20 to 26 hours, washing the obtained product with ethanol and deionized water successively until neutral, and obtaining a primary doped polyaniline-carbon nanotube composite material after drying and grinding; wherein the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture is 15 to 25:1;

[0076] (4) adding excess ammonia water to the primary doped polyaniline-carbon nanotube composite material for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 20 to 26 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-carbon nanotube composite material;

[0077] (5) The intrinsic polyaniline-graphene composite material and the intrinsic polyaniline-carbon nanotube composite material were added to a 1 mol / L doped acid solution in a mass ratio of 1:1, mixed and stirred, and then allowed to stand for 20 to 26 hours. After that, they were filtered and washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain the nanocarbon secondary doped polyaniline composite material.

[0078] Furthermore, the mass ratio of aniline to graphene in the aniline-graphene mixture is 20:1, and the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture is 20:1. The doping acid solution is one of an inorganic acid solution, an organic acid solution and a composite acid, and the molar concentration ratio of the inorganic acid to the organic acid in the composite acid is 1:1 to 1:6. The morphology of the composite material of graphene, carbon nanotubes and secondary doped polyaniline prepared by the method of secondary doping of polyaniline is more uniform, and the nanofibers are more uniform. The product morphology is best when the ratio of RGO to ANI is 1:20 and the ratio of CNTs to ANT is 1:20. PANI wraps CNTs neatly arranged on the graphene surface, with uniform size and fiber length reaching 850nm.

[0079] Preferably, the metal surface rust-proof coating provided by the embodiment of the present invention comprises 0.3% to 0.6% by mass of the nano-carbon secondary doped polyaniline composite material, which can not only improve the anti-corrosion performance of the coating through the anti-pitting and passivation effects of the polyaniline composite material, but also need to take into account that the compactness of the coating will not be destroyed.

[0080] Specifically, the mass percentage of the nano-carbon secondary doped polyaniline composite material included in the metal surface rust anti-corrosion coating is 0.5%. The mass percentage of the long-acting rust conversion agent included in the metal surface rust anti-corrosion coating is 3%. At this ratio, the anti-corrosion performance of the coating is enhanced, and it may take a longer time to observe the difference in the salt spray test because the coating effect is better.

[0081] The anti-rust coating for metal surfaces prepared in the embodiment of the invention was applied to the treated rusted steel and low-carbon steel surfaces by brushing, and the coating thickness was (485±25) μm. After drying for 7 days at room temperature until it was completely cured, basic physical properties tests, water contact angle tests, AC impedance tests and neutral salt spray tests were carried out. The difference between the anti-rust coatings for metal surfaces used in the experiment was only the different added mass percentages of the nano-carbon secondary doped polyaniline composite material.

[0082] Table 3 Basic physical properties of coatings with different addition amounts of nanocarbon secondary doped polyaniline composites

[0083]

[0084]

[0085] The coatings prepared by the five different addition amounts of nanocarbon secondary doped polyaniline composite materials were tested for fineness, hardness and impact resistance, and the drying time of the coatings was observed. At the same time, the coatings without composite materials were set as the control group. The test results are shown in Table 6. The results show that the addition of different amounts of nanocarbon secondary doped polyaniline composite materials has a small overall effect on the physical properties of the coating. Among them, the fineness of the coating is below 35μm, which shows that it is not easy to deposit in the nanocarbon secondary doped polyaniline composite materials, and the two have good miscibility. It can be seen from Table 3 that the fineness of the coating gradually increases with the increase of the composite material. This is because the increase of the nanocarbon secondary doped polyaniline composite material increases the grinding time, thereby affecting the degree of dispersion and increasing the fineness. The addition amount of nanocarbon secondary doped polyaniline composite material has little effect on the hardness and impact resistance of the coating, especially when the addition amount is small, it remains basically unchanged, but the addition amount increases slightly from 0.5wt.% to 1wt.%, indicating that the addition of nanocarbon secondary doped polyaniline composite materials will not affect the physical properties of the coating, but will also fill the gaps in the coating and reduce its defects.

[0086] Table 4 AC impedance fitting results based on different immersion times of bare steel sample coating

[0087]

[0088] from Fig.11 Based on the schematic diagram of the AC impedance results of the bare steel sample coating and Table 4, it can be seen that the impedance value of the coating is different when the addition amount of the nanocarbon secondary doped polyaniline composite material is different. When the addition amount is 0.05wt.%, the nanocarbon secondary doped polyaniline composite material is most easily dispersed in the coating and can play a certain shielding role, but due to the small content, the role that can be played is limited, and the excessive distribution makes it impossible to form a complete conductive path in the coating, which is not conducive to the formation of a passivation film. Therefore, the anti-corrosion effect of the coating is not significantly improved. When the addition amount of the nanocarbon secondary doped polyaniline composite material is 0.1wt.% and 0.5wt.%, the anti-corrosion ability of the coating is significantly improved. This is because the content of the nanocarbon secondary doped polyaniline composite material increases, which increases the density of its distribution in the coating, can form a conductive path to accommodate the electrons transferred from the metal matrix, and enhance the shielding effect of the coating. At the same time, the nanocarbon secondary doped polyaniline composite material can also make up for the defects of the coating, block the corrosive medium from penetrating the coating along the gap, and prevent the coating from being damaged and losing its ability to protect the metal matrix. As the content of nanocarbon secondary doped polyaniline composite material continues to increase, the shielding performance begins to decrease. This is because too much composite material content will form agglomerates that are not conducive to dispersion, and will also destroy the density of the coating, which will have a great impact on the shielding performance of the coating. Therefore, during the entire immersion process, as the immersion time increases, the coating is continuously eroded by corrosive media, which will reduce the anti-corrosion performance of the coating. Fig.11 The impedance arc radius of the Nyquist diagram decreases, and the Bode low-frequency impedance modulus decreases, but the overall decrease degree decreases, especially for the coating with an addition amount of 0.5wt.%. As can be seen from Table 4, after immersion for 3000h, the impedance value can still reach 7.643×1010Ω·cm2, which is 85.32% higher than the impedance value of the coating without polyaniline composite material. This shows that the nanocarbon secondary doped polyaniline composite material can be added to the rusty coating in an appropriate amount to enhance the anti-corrosion performance of the coating and provide excellent protection for the metal substrate.

[0089] Table 5 AC impedance fitting results based on different immersion time of rusted steel sample coating

[0090]

[0091] Fig.12 The following is a comparison of the AC impedance results of the rusted steel sample coating. Fig.12 As can be seen from Table 5, during the entire immersion process, the coating based on the rusted steel sample Fig.11 The electrochemical changes of the coating on the bare steel sample are consistent with those shown in the figure. In the initial stage of immersion, the Nyquist impedance arc radius is large, the Bode impedance modulus curve is approximately a straight line, and the impedance values ​​of all coatings are higher than 2×1011Ω·cm 2 The impedance values ​​of each coating are 0.5wt.%>1wt.%>0.1wt.%>0.05wt.%>0wt.%>2wt.%. As the immersion time increases, the impedance arc radius in the Nyquist diagram and the low-frequency impedance modulus in the Bode diagram begin to decrease, but the 0.5wt.% coating always maintains the highest impedance. Even after immersion for 3000h, the impedance value remains above 1010Ω·cm2, achieving long-term protection for the metal substrate.

[0092] The AC impedance fitting results of different coatings and different samples at different times are plotted into bar graphs, such as Fig.13 As shown, the added mass percentages of the nanocarbon secondary doped polyaniline composite material are: (a) 0wt.%; (b) 0.05wt.%; (c) 0.1wt.%; (d) 0.5wt.%; (e) 1wt.%; (f) 2wt.%. It can be seen from the figure that regardless of whether it is a coating based on a bare steel sample or a rusted steel sample, the impedance value decreases with the increase of the immersion time, and the impedance value of the rusted steel sample coating is always higher than that of the bare steel sample. The coating with an addition amount of 2wt.% has a relatively low improvement, indicating that excessive addition of the nanocarbon secondary doped polyaniline composite material will not only reduce the binding ability with the epoxy resin, but also may affect the performance of the rust conversion agent.

[0093] Combination Fig.11 and Fig.12 Overall, the addition of nanocarbon secondary doped polyaniline composite materials can improve the anti-corrosion performance of the coating, and the rusty coating still maintains a good rust layer conversion ability, indicating that the addition of an appropriate amount of nanocarbon secondary doped polyaniline composite materials can ensure the rust conversion of the coating while enhancing the shielding and anti-corrosion properties of the coating, extending the penetration path of the corrosive medium, and the coating system provides effective protection for rusty metal substrates.

[0094] Fig.14 and Fig.15 The results of neutral salt spray tests on bare steel and rusted steel samples were shown in Figure 1, where the mass percentages of the nanocarbon secondary doped polyaniline composite materials added were: a. 0.05wt.%; b. 0.1wt.%; c. 0.5wt.%; d. 1wt.%; e. 2wt.%. It can be seen that the coatings were corroded to varying degrees after 1440 hours of testing in the salt spray test chamber, and the coating with 2wt.% of the nanocarbon secondary doped polyaniline composite material was relatively severely corroded, with more rust products near the scratches, especially the coating of the bare steel sample also had bubbling, indicating that excessive addition of the nanocarbon secondary doped polyaniline composite material would destroy the original anti-corrosion ability of the coating, resulting in a decrease in coating performance. The surface condition of the coatings with other additions is relatively good, especially the coating with an addition of 0.5wt.%, which has almost no trace of corrosion. This is mainly due to the addition of the nanocarbon secondary doped polyaniline composite material, which prolongs the penetration path of the corrosive medium and delays the contact time between the corrosive medium and the metal matrix. At the same time, the appropriate amount of nanocarbon secondary doped polyaniline composite material can also form a conductive path in the coating that can accommodate a large number of electrons, so that the passivation and shielding effects of the coating are enhanced. Fig.14 and Fig.15 It can be found that the same coating coated on samples in different states will have different corrosion conditions. The corrosion degree of the rusted steel sample is relatively lighter than that of the bare steel sample, which is consistent with the results of the electrochemical AC impedance test. It proves that the appropriate addition of nano-carbon secondary doped polyaniline composite materials can not only increase the shielding performance of the coating against corrosive media, but also will not have much effect on the rust-proofing ability of the coating, which generally improves the protection of the coating to the metal substrate.

[0095] Through the above performance analysis, the following conclusions are drawn:

[0096] (1) By testing the basic properties of the coating, it was found that the basic physical properties of the coating did not change much overall when different amounts of nanocarbon secondary doped polyaniline composite materials were added, and all remained in a good state. Among them, the hardness and impact resistance of the coating with an addition amount of 0.5wt.% and 1wt.% were relatively high.

[0097] (2) Through the AC impedance test results and neutral salt spray test results of the coating, it can be found that the addition of nanocarbon secondary doped polyaniline composite materials has a certain effect on the anti-corrosion performance of the coating. Among them, the coating with an addition amount of 0.5wt.% has the highest impedance value. After 3000h of immersion, the coating impedance value still remains above 1011Ω·cm2, and after 1440h of salt spray test, the coating has no bubbling and shedding phenomena, which proves that the nanocarbon secondary doped polyaniline composite material can be well combined with the rusty coating, improve the overall anti-corrosion performance, and achieve effective protection of the metal substrate.

[0098] (3) After comparative analysis, it can be found that the impedance value of the coating based on the rusted steel sample is higher than that of the bare steel sample coating, and after 1440 hours of neutral salt spray test, there is no obvious corrosion on the surface of the rusted steel sample coating, indicating that the nanocarbon secondary doped polyaniline composite material can fill the pores of the coating, enhance the barrier ability of the coating, and effectively inhibit the contact between the corrosive medium and the metal. In addition, the passivation effect of the nanocarbon secondary doped polyaniline composite material can produce a synergistic effect with the protective film formed by the chelation of tannic acid, which prolongs the penetration channel of the corrosive medium and improves the anti-corrosion performance of the coating.

[0099] The invention provides a metal surface rust anticorrosion coating in which the addition mass percentage of a nano-carbon secondary doped polyaniline composite material is 0.2% to 0.6%. When the addition amount of the nano-carbon secondary doped polyaniline composite material is less than the range, the effect that can be exerted is limited, and the over-dispersion leads to failure to form a complete conductive path in the coating, which is not conducive to forming a passivation film, so the anticorrosion effect of the coating is not significantly improved; when the addition amount of the nano-carbon secondary doped polyaniline composite material is within the ratio range, the anticorrosion ability of the coating is significantly improved, the distribution density of the nano-carbon secondary doped polyaniline composite material in the coating is increased, a conductive path can be formed to accommodate electrons transferred from a metal matrix, and the shielding effect of the coating is enhanced. At the same time, the polyaniline composite material can also make up for coating defects, block corrosive media from penetrating the coating along gaps, and prevent the coating from being damaged and losing its protective ability to the metal matrix. The long-acting rust converter uses tannic acid, gallic acid and salicylic acid at the same time. Tannic acid, gallic acid and salicylic acid can cooperate with each other to form a strong complex layer with the already formed metal oxide or the metal itself through chelation. The synergistic effect of the three corrosion inhibitors, tannic acid, gallic acid and salicylic acid, enhances the synergistic migration protection effect, and can form a relatively dense and smooth conversion film on the surface of the rusted metal. The formed conversion film can effectively prevent the corrosive medium from penetrating and contacting the metal. It is suitable for steel structures, especially for steel structure connection parts. It has good permeability and high rust conversion efficiency. It can convert harmful rust into a protective layer that is beneficial to corrosion prevention, provide effective protection for the metal matrix, and the anti-corrosion effect can reach more than 20 years, eliminating the need for more frequent maintenance, saving resources and manpower and material resources, and having significant economic benefits.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A rust-proof coating for metal surfaces, characterized in that: The metal surface rust anti-corrosion coating comprises 20% to 50% by mass of an active diluent, 10% to 30% by mass of an epoxy resin, 4% to 10% by mass of zinc phosphate, 2% to 10% by mass of tannic acid, 0.2% to 0.6% by mass of a nano-carbon secondary doped polyaniline composite material and 0.1% to 5% by mass of a long-acting rust converter, wherein the nano-carbon secondary doped polyaniline composite material is composited by secondary doping of polyaniline with a mass ratio of 15 to 25:1:15 to 25 for aniline, graphene and carbon nanotubes.

2. The metal surface rust anticorrosion coating according to claim 1, characterized in that: The long-acting rust conversion agent includes 30% to 50% by mass of carrier oil, 1% to 4% by mass of osmotic stabilizer, 6% to 10% by mass of slow-release carrier, 3% to 5% by mass of sterilizer, 1% to 2% by mass of antioxidant, 2% to 6% by mass of thixotropic agent, 10% to 20% by mass of tannic acid, 9% to 15% by mass of salicylic acid, and 6% to 20% by mass of gallic acid, wherein the total mass percentage of tannic acid, salicylic acid and gallic acid contained in the long-acting rust conversion agent is 25% to 50%.

3. The metal surface rust anticorrosion coating according to claim 1, characterized in that: The mass percentage of tannic acid contained in the long-acting rust conversion agent is 13% to 15%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent is 11% to 12%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent is 10% to 15%.

4. The metal surface rust anticorrosion coating according to claim 1, characterized in that: The mass percentage of tannic acid contained in the long-acting rust conversion agent is 14%, the mass percentage of salicylic acid contained in the long-acting rust conversion agent is 11.5%, and the mass percentage of gallic acid contained in the long-acting rust conversion agent is 13%.

5. The metal surface rust anticorrosion coating according to any one of claims 1 to 4, characterized in that: The nano-carbon secondary doped polyaniline composite material is prepared by the following method: (1) Two equal volumes of 1 mol / L doped acid solutions were added to an aniline-graphene mixture and ammonium persulfate, wherein the molar ratio of the aniline-graphene mixture to the ammonium persulfate was 0.8:1, and the two were uniformly mixed with a magnetic stirrer for 1-2 h, and allowed to stand at room temperature for 20-26 h. The obtained product was washed with ethanol and deionized water successively until neutral, and dried and ground to obtain a primary doped polyaniline-graphene composite material; wherein the mass ratio of aniline to graphene in the aniline-graphene mixture was 15-25:1; (2) adding excess ammonia water to the primary doped polyaniline-graphene composite material for dedoping, stirring with a magnetic stirrer for 1-2 h, standing at room temperature for 20-26 h, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-graphene composite material; (3) Two equal volumes of 1 mol / L doped acid solutions were added to the aniline-carbon nanotube mixture and ammonium persulfate, wherein the molar ratio of the aniline-carbon nanotube mixture to the ammonium persulfate was 0.8:1, and the two were uniformly mixed with a magnetic stirrer for 1-2 h, and allowed to stand at room temperature for 20-26 h. The obtained product was washed with ethanol and deionized water successively until neutral, and dried and ground to obtain a primary doped polyaniline-carbon nanotube composite material; wherein the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture was 15-25:1; (4) adding excess ammonia water to the primary doped polyaniline-carbon nanotube composite material for dedoping, stirring with a magnetic stirrer for 1-2 h, standing at room temperature for 20-26 h, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain an intrinsic polyaniline-carbon nanotube composite material; (5) The intrinsic polyaniline-graphene composite material and the intrinsic polyaniline-carbon nanotube composite material were added to a 1 mol / L doped acid solution in a mass ratio of 1:1, mixed and stirred, and allowed to stand for 20 to 26 h. They were then filtered and washed with ethanol and deionized water in turn until neutral. Finally, they were dried and ground to obtain the nanocarbon secondary doped polyaniline composite material.

6. The metal surface rust anticorrosion coating according to claim 6, characterized in that: The mass ratio of aniline to graphene in the aniline-graphene mixture is 20:1, and the mass ratio of aniline to carbon nanotubes in the aniline-carbon nanotube mixture is 20:

1.

7. The metal surface rust-proof coating according to claim 6, characterized in that: The mass percentage of the nano-carbon secondary doped polyaniline composite material included in the metal surface rust anti-corrosion coating is 0.3% to 0.6%.

8. The metal surface rust anticorrosion coating according to claim 6, characterized in that: The mass percentage of the nano-carbon secondary doped polyaniline composite material included in the metal surface rust anti-corrosion coating is 0.5%.

9. The metal surface rust anticorrosion coating according to claim 6, characterized in that: The mass percentage of the long-acting rust conversion agent included in the metal surface rust anti-corrosion coating is 3%.

Citation Information

Patent Citations

  • Environment-friendly solvent-free humidified and rusted anticorrosive paint

    CN101747825A

  • Water-based polyaniline composite epoxy rusted anti-corrosion paint and preparation method thereof

    CN103450762A

  • Waterborne residual rust antirust coating and preparation method thereof

    CN103897510A

  • Multi-carboxyl epoxy resin rust-stabilizer

    CN103992722A

  • Antirust coating and preparation method thereof

    CN105885644A